Portraying the Use of English Instructional Media Used By English Teachers in EFL Classroomat SMKN in Gorontalo Regency - Suleman Mayang (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2023)
Instructional media are important to assist the instruction and facilitate the students' achievement in learning English. The aims of this research are firstly to investigate the use of English instructional media delivered by English teacher in EFL classroom at SMKN in Gorontalo Regency. Secondly, to explore the problems that the teacher encounter in implementing instructional media in EFL classroom at SMKN in Gorontalo Regency. Thirdly, to find out the strategies to solve the teacher problems in using the instructional media in EFL classroom at SMKN in Gorontalo Regency. The participants are three English teachers from each school and some students from three classes. By using qualitative method, the researcher did observation, interview and document analysis in the technique of collecting the data. Moreover, the finding shows that the types of instructional media used by the teachers were audio visual media and non-print media. Audio visual media like picture from LCD, whereas print media like whiteboard, books and photocopy. In conclusion, the teaching and learning process at SMK Batudaa and SMK 1 and 2 of Limboto still need improvement because teachers had less ability in applying the media, the availability the media in every school were not conducive and the government did not make some workshop to develop teacher competency in using instructional media. Thus, this study recommended that for the parties to improve this condition in order to improve the educational process in every school in Gorontalo Regency.